Sistem Penyiraman Pintar dan Monitoring Tanaman Sawi Otomatis Berbasis Esp 32 dan Sensor Kelembapan Tanah Menggunakan Metode Fuzzy Mamdani - Pamungkas, Rizky; Ullah, Aulia; Faizal, Ahmad; Zarory, Hilman (Universitas Al Azhar Indonesia, 2025)
Agriculture is an important sector in the Indonesian economy, with vegetables such as mustard greens (Brassica juncea) that have high economic value and are important for the healthy diet of the community. One of the main challenges in mustard cultivation is the optimal management of soil moisture, as unstable moisture levels can affect the quality and quantity of the harvest. This research aims to design and implement an automatic irrigation system based on Internet of Things (IoT) technology using the ESP32 microcontroller and soil moisture sensors, as well as applying Mamdani Fuzzy logic to manage irrigation adaptively. This system is capable of increasing water usage efficiency by up to 50% by maintaining soil moisture at optimal levels, which positively impacts the growth of mustard plants. In addition, this system allows for remote monitoring through an IoT application, making it easier for farmers to manage irrigation more efficiently. The research results show that the implementation of this automated system not only reduces dependence on manual labor but also ensures more efficient water usage, thereby providing an innovative solution for irrigation efficiency in the agricultural sector. Keywords - ESP32, Mamdani Fuzzy, Smart Irrigation System, Soil Moisture.